Factors Influencing Middle School Students' Learning Motivation in Physical Education: Literature Review - Kamaludin, Yudi Ahmad; Marwan, Iis; Juniar, Dicky Tri (JUMORA: Jurnal Moderasi Olahraga, 2026)
Student motivation is a key determinant of engagement and learning outcomes in junior high school Physical Education (PE), yet evidence indicates a decline in motivation during early adolescence. This study aimed to synthesize empirical findings on factors influencing students’ motivation in PE learning. A systematic literature review was conducted on 15 studies published between 2020 and 2025 and indexed in Scopus, Google Scholar, ERIC, and DOAJ. Data were analyzed using thematic analysis. The results reveal that student motivation is influenced by three main domains: pedagogical, internal psychological, and social factors. Pedagogical factors particularly teacher autonomy support, activity variety, and mastery-oriented learning climates emerged as the most influential determinants of autonomous motivation and engagement. Internal psychological factors, such as perceived competence and task value, acted as key mediators, while social support from peers and families strengthened motivation indirectly. This review highlights the importance of student-centered instructional practices in enhancing motivation in junior high school Physical Education and suggests the need for longitudinal and intervention-based research, especially within the Indonesian context